2015
DOI: 10.1177/0022034515613043
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-138 Inhibits Periodontal Progenitor Differentiation under Inflammatory Conditions

Abstract: Inflammatory conditions as they occur during periodontal disease often result in decreased alveolar bone levels and a loss of connective tissue homeostasis. Here we have focused on the effect of microRNA-138 (miR-138) as a potential regulator of periodontal stem cells as they affect homeostasis during inflammatory conditions. Our data indicate that miR-138 was significantly upregulated in our periodontal disease animal model. Interaction of miR-138 with a predicted targeting site on the osteocalcin (OC) promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 43 publications
1
32
0
Order By: Relevance
“…In the present study, miR-138 was responsible for the tissue damage and organ dysfunction induced by LPS. A previous study showed that miR-138 is increased due to inflammation situation in periodontitis model or in endothelial cells under stimulation with LPS [29,30], but miR-138 is only considered as a consequence of inflammation in these two studies. In the present study, we found that miR-138 not only increased as a result of inflammation but also acted as a regulator by targeting SIRT1, thus providing a potential target for sepsis treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, miR-138 was responsible for the tissue damage and organ dysfunction induced by LPS. A previous study showed that miR-138 is increased due to inflammation situation in periodontitis model or in endothelial cells under stimulation with LPS [29,30], but miR-138 is only considered as a consequence of inflammation in these two studies. In the present study, we found that miR-138 not only increased as a result of inflammation but also acted as a regulator by targeting SIRT1, thus providing a potential target for sepsis treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have proved that miRNAs could be critical regulators in bone remodeling and inflammatory response such as periodontitis . The aberrant miRNA expression reacting to pathologic products, in turn, affects periodontitis . In our previous studies, it has been shown that microRNA‐335‐5p (miR‐335‐5p) could promote osteoblast differentiation and bone regeneration in vitro and in miR‐335‐5p transgenic (335‐Tg) mice via inhibiting DKK1, a Wnt pathway antagonist, which have been well‐characterized .…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] The aberrant miRNA expression reacting to pathologic products, in turn, affects periodontitis. [9][10][11] In our previous studies, it has been shown that microRNA-335-5p (miR-335-5p) could promote osteoblast differentiation and bone regeneration in vitro and in miR-335-5p transgenic (335-Tg) mice via inhibiting DKK1, a Wnt pathway antagonist, which have been well-characterized. [3][4][5] Besides, several studies have reported the inhibitive effects of miR-335-5p on bone-related disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Periodontitis is a set of chronic inflammatory disease of the periodontium, and aberrant miRNA expression may aggravate the disease progression (Xie et al, ). Previous studies have suggested that several miRNAs were abnormal expression in the progress of periodontal disease and regulated multifarious genes such as RUNX2, osteocalcin (OC), and EGFR (Motedayyen, Ghotloo, Saffari, Sattari, & Amid, ; Xie et al, ; Zhou et al, ). MiR‐218, a tumour suppressor, is significantly downregulated in various cancers (Deng et al, ; Shi et al, ) and inflammatory disorders (Xu et al, ).…”
Section: Discussionmentioning
confidence: 99%